STEAM Approach to Technology Education - Zaynitdinovna, Bakhritdinova Dilobar (International Journal on Integrated Education, 2023)
V state description of methods and methods of training technologies and methods of teaching of various subjects in public schools, transition to innovative educational process and teaching of aesthetic sciences with consideration of the need for intensive language, IKT and new methods of training, and STEAM-pedagogical basics, the method of formation of necessary basic knowledge for the acquisition of new professional competence.